Quantitative detection of human- and canine-associated Bacteroides genetic markers from an urban coastal lagoon - Serhat A. Yasar (IWA Publishing, 2021)
The contamination of water catchments by nonpoint source faecal pollution is a major issue affecting the microbial quality of receiving waters and is associated with the occurrence of a range of enteric illnesses in humans. The potential sources of faecal pollution in surface waters are diverse, including urban sewage leaks, surface runoff and wildlife contamination originating from a range of hosts. The major contributing hosts require identification to allow targeted management of this public health concern. In this study, two high-performing Microbial Source Tracking (MST) assays, HF183/Bac242 and BacCan-UCDmodif, were used for their ability to detect host-specific Bacteroides 16Sr RNA markers for faecal pollution in a 12-month study on an urban coastal lagoon in Sydney, Australia. The lagoon was found to contain year-round high numbers of human and canine faecal markers, as well as faecal indicator bacteria counts, suggesting considerable human and animal faecal pollution. The high sensitivity and specificity of the HF183/Bac242 and BacCan-UCDmodif assays, together with the manageable levels of PCR inhibition and high level DNA extraction efficiency obtained from lagoon water samples make these markers candidates for inclusion in an MST ‘toolbox’ for investigating host origins of faecal pollution in urban surface waters. HIGHLIGHTS This long-term study (twelve months with bi-monthly sampling) validated the use of HF183/BacCan242 and BacCan-UCDmodif to quantify host-associated faecal inputs in urban surface waters.; Correlations between MST markers, traditional FIB measurements, and physiochemical parameters indicate that the latter may be used to predict the likelihood of human- and canine-associated faecal inputs at this site.;